ANALYSIS TOOL OVERHANG IN THE MACHINE CNC ET-242 ON SURFACE ROUGHNESS WITH VARIATION OF FEEDING - Febi Rahmadianto; Dadang Hermawan (Widyagama University of Malang, 2018)
Lathe is a process to get the shape of the cylindrical workpiece by rotating the workpiece on the spindle and moving the chisel towards the workpiece. To be able to screw the workpiece of the chisel should hang and extend from the turret. The length of the hanging chisel is called the tool overhang (Zelinski, 2005: 1). There is no definite hint of setting the tool overhang and only adjusted between the position of the turret and workpiece. In order to achieve a good surface roughness, usually the overhang tool is arranged to a minimum.In this study the independent variables used are the tool overhang 14 mm, 21 mm, 28 mm, 35mm and feeding 0.15 mm rotation-1, 0.25 mm rotation -1, 0.35 mm. rotation -1. The measured dependent variable is the surface roughness of the workpiece.From the results of testing and data analysis can be concluded that the tool overhang effect on the roughness of the workpiece surface results of the process of lathe in various variations of feeding (feeding). The longer the tool overhang and the greater the feeding motion will result in greater surface roughness. The lowest surface roughness was obtained from a 14 mm long overhang tool and feeding 0.15 mm rotation-1.Keywords : Machine CNC ET-242, Surface Roughness, Feeding Variation.